The ghostkeeper - Taylor, Johanna; Myers, Micah (2024)
"A gothic graphic novel that follows a young medium with the gift--or curse, as some might say--to communicate with the dead"--
Ages 12 years and up.
Keywords: Graphic novels; Mediums -- Fiction; Ghosts -- Fiction; Supernatural -- Fiction; Ghost comics; Paranormal comics; Graphic novels